Testicular evisceration sequel to trauma and its surgical management in a rabbit - Degu, Nurhusien Yimer; Bukar, Mohammad Modu; Awang Kamaludin, Dayang Norhaizum; Sarsaifi, Kazhal; Mohd Said, Nur Ain Shafiqah (Department of Veterinary Services Malaysia, 2015)
The characteristic thin skin of the scrotal sac in a rabbit was torn resulting in traumatic exposure of the right testicle. Bilateral orchiectomy through an open scrotal approach was performed under general anaesthesia. The rabbit was premedicated with Acepromazine (0.5 mg/kg, 0.15 ml) and Flunixin meglumine (1 mg/kg, 0.03 ml,) intra-muscularly. Isoflurane was used for induction at 5% with O2 flow rate at 0.7 L/min and maintenance Isoflurane, 1.5% - 3%, O2 flow rate = 0.7 L/min) of general anaesthesia. Both right and left testicles were removed and the hemiscrotal incision was closed with 4-0 Vicryl, horizontal mattress suture pattern. Post-operative treatments with antibiotic and anti-inflammatory agents were instituted and the client was advised about how to safely manage aggressive behaviour of rabbits towards each other. The surgical site healed without complication and the neutered rabbit recovered fully within 14 days.